A 2‐stage ovarian cancer screening strategy using the Risk of Ovarian Cancer Algorithm (ROCA) identifies early‐stage incident cancers and demonstrates high positive predictive value. Issue 19 (26th August 2013) - Lu, Karen H.; Skates, Steven; Hernandez, Mary A.; Bedi, Deepak; Bevers, Therese; Leeds, Leroy; Moore, Richard; Granai, Cornelius; Harris, Steven; Newland, William; Adeyinka, Olasunkanmi; Geffen, Jeremy; et al.
Abstract : BACKGROUND: A 2‐stage ovarian cancer screening strategy was evaluated that incorporates change of carbohydrate antigen 125 (CA125) levels over time and age to estimate risk of ovarian cancer. Women with high‐risk scores were referred for transvaginal ultrasound (TVS). METHODS: A single‐arm, prospective study of postmenopausal women was conducted. Participants underwent an annual CA125 blood test. Based on the Risk of Ovarian Cancer Algorithm (ROCA) result, women were triaged to next annual CA125 test (low risk), repeat CA125 test in 3 months (intermediate risk), or TVS and referral to a gynecologic oncologist (high risk). RESULTS: A total of 4051 women participated over 11 years. The average annual rate of referral to a CA125 test in 3 months was 5.8%, and the average annual referral rate to TVS and review by a gynecologic oncologist was 0.9%. Ten women underwent surgery on the basis of TVS, with 4 invasive ovarian cancers (1 with stage IA disease, 2 with stage IC disease, and 1 with stage IIB disease), 2 ovarian tumors of low malignant potential (both stage IA), 1 endometrial cancer (stage I), and 3 benign ovarian tumors, providing a positive predictive value of 40% (95% confidence interval = 12.2%, 73.8%) for detecting invasive ovarian cancer. The specificity was 99.9% (95% confidence interval = 99.7%, 100%). All 4 women with invasive ovarian cancer were enrolled in the study for at least 3 years with low‐risk annual CA125 test values prior to rising CA125 levels. CONCLUSIONS: ROCA followed by TVS demonstrated excellent specificity and positive predictive value in a population of US women at average risk for ovarian cancer. Cancer 2013;119:3454–3461. . © 2013 American Cancer Society . Abstract : This study evaluated a 2‐stage ovarian cancer screening strategy incorporating the Risk of Ovarian Cancer Algorithm (ROCA). ROCA identified early‐stage incident cases with excellent specificity and highlights the potential for implementing effective strategies for the early detection of ovarian cancer in postmenopausal women.